Pengaruh Work-Life Balance terhadap Kepuasan dan Kinerja Karyawan - Ading Rahman Sukmara (Jurnal Manajemen Kewirausahaan dan Teknologi, 2026)
This research focuses on the strategic role of the people's market as a driver of the regional economy and a source of Regional Original Income (PAD), by taking a case study of the arrangement of the people's market by the Ciamis Regency MSME Office. Using a qualitative approach, data was collected through observation, interviews, and documentation studies. The results of the study show that the Regional Government of Ciamis Regency implements five main strategies in structuring the people's market, including optimizing development and revitalization with ease of access, market development based on potential and local characteristics, cooperation with investors, facilitation and guaranteeing the ease of capital lending through banking, and market promotion using digital technology. This strategy has a significant impact on the achievement of PAD. The achievement of PAD from the people's market sector of Ciamis Regency was recorded to exceed the target in the period of 2015 to 2017, reaching 113.4%, 128.0%, and 121.9%, respectively, although it decreased in 2018 to 87.2%. To optimize regional levy revenue, these findings conclude the need to improve and improve the regional levy management system to support the performance of the apparatus, the implementation of routine activities such as coordination between agencies and socialization to business actors, as well as increasing the discipline, dedication, and honesty of fiscal officials in carrying out their main duties and functions proportionately.